2019
DOI: 10.1002/eat.23086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the reciprocal relationships between adolescents' perceptions of parental and peer attachment and disordered eating: A multiwave cross‐lagged panel analysis

Abstract: Objective: This prospective study explored bidirectional associations between attachment quality towards mother, father, and peers and disordered eating among a large population-based sample of boys and girls in the transition from preadolescence to adolescence. Specifically, we examined whether insecure attachment relationships emerged as a risk factor for or as an outcome of disordered eating.Method: A population-based sample of 904 adolescent girls and boys was assessed four times, at baseline (T1; M age = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Higher paternal anxiety and avoidance, and maternal avoidance predicted lower body satisfaction in both genders. A recent meta-analysis (Cortés-García et al, 2019b) highlighted the differential and gender-specific contribution of attachment figures on the development of disordered eating in adolescence. They concluded that positive attachment to parents, primarily mothers, leads to less eating problems.…”
Section: Discussionmentioning
confidence: 99%
“…Higher paternal anxiety and avoidance, and maternal avoidance predicted lower body satisfaction in both genders. A recent meta-analysis (Cortés-García et al, 2019b) highlighted the differential and gender-specific contribution of attachment figures on the development of disordered eating in adolescence. They concluded that positive attachment to parents, primarily mothers, leads to less eating problems.…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted thus far shows that the insecure attachment pattern/style and abnormal bonding with parents are factors contributing to the development of eating disorders (26)(27)(28)(29). Cortés-García et al (5) performed a meta-analytic review of studies on how insecure attachment leads to symptoms of eating disorders, through mediation analysis. Maladaptive emotion regulation and depressive symptoms were found to be among the major pertaining factors, while body dissatisfaction, neuroticism, perfectionism, mindfulness, and social comparison were of somewhat lesser importance.…”
Section: Family Factors Related To Eating Disordersmentioning
confidence: 99%
“…The significant role of the Westernization phenomenon and the increased incidence of eating disorders (anorexia and bulimia) in today's adolescent population indicate the need to implement health prevention measures aimed at rapid detection of psycho-social protective factors, as well as recognition of the risk of developing eating disorders (1)(2)(3). Research done in recent years concerning problems connected with eating disorders has confirmed the significance of both gender and age as two main risk factors for developing eating disorders: such disorders are prevalent in girls and young women (4,5). Besides gender and age, literature on the subject also lists a variety of other eating disorder risk factors: family environment, including attachment and bonding with parents; body image, including body shape dissatisfaction; low selfesteem; psychological distress; negative peer relationships; and family and media pressure (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews have indicated that insecure attachment forecasts disordered eating during the transition to adolescence (Gander et al, 2015;Jewell et al, 2016). This assertion has been demonstrated in long term follow-up studies (Cortés-García, Hoffmann, Warschburger, & Senra, 2019;Le Grange et al, 2014;Milan & Acker, 2014). Even though the insecure attachment-EDs link is established, less is know about processes responsible for the association.…”
Section: Depressive Symptoms In Adolescence?mentioning
confidence: 99%